Production and performance of larvae and spat of pure and hybrid species of Mytilus chilensis and M. galloprovincialis from laboratory crosses Producción y comportamiento de larvas de especies puras e híbridas entre Mytilus chilensis y Mytilus galloprovincialis obtenidas en laboratorio - Jorge E Toro; Pablo A Oyarzún; Carolina Peñaloza; Angélica Alcapán; Viviana Videla; Jorge Tillería; Marcela Astorga; Víctor Martínez (Latin American Journal of Aquatic Research, 2012)
Adult specimens of M. galloprovincialis from Concepción Bay and M. chilensis from Yaldad Bay, Chile, were transferred to the laboratory to produce crosses of "pure" and "hybrid" species in order to evaluate early larval development and growth. These variables are important for understanding the dynamics of these two mussel species in this potential hybrid zone where they occur sympatrically. The study showed that fertilization occurred in all crosses and significant differences were not detected between pure lines and hybrids in terms of the percentage of eggs that developed into larvae. Hybrid larvae and spat from both reciprocal crosses grew significantly more than those from pure lines, although valve length values were within the ranges reported in the literature. Ejemplares adultos de M. galloprovincialis de la bahía de Concepción y de M. chilensis de la bahía de Yaldad, Chile, se trasladaron al laboratorio para realizar cruzamientos puros de cada especie e híbridos, para evaluar el desarrollo larval temprano y su crecimiento. Estas variables son importantes para entender la dinámica de estas dos especies de mitílidos en esta potencial zona híbrida donde se encuentran en forma simpátrica. El estudio mostró que la fertilización ocurrió en todos los cruzamientos y no se detectó diferencias significativas entre líneas puras e híbridas en el porcentaje de huevos que se desarrollaron a larvas. Las larvas y juveniles híbridos de ambos cruzamientos recíprocos crecieron significativamente más que las larvas de los cruzamientos de especies puras, aunque los valores de longitud de la valva están dentro de los rangos reportados en la bibliografía.